The Representation of Palestinian children in Indonesian local and international online news: A Transitivity analysis - Mentari Antika Putri; Ilma Yullinda Rahmah; Muhammad Nur Assyddyq; Faza Hannan Purinanda (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This study investigates how Indonesian local and international news outlets represent Palestinian children through language during news coverage of the Palestine and Israel conflict after October 7, 2023, in which more than 14,000 children were affected. Despite the mass coverage of the conflict, there is still very little comparative research that closely examines how different online media contexts portray Palestinian children, especially one that is comparing Indonesian and Western outlets. This study used a qualitative descriptive approach based on Systemic Functional Linguistics (SFL), by applying transitivity analysis to analyze process types, participant roles, semantic fields, and circumstantial elements in 289 clauses. The data were taken from six selected news articles published between October 2024 and May 2025. The data were retrieved from two Indonesian outlets (Kompas.com and The Jakarta Post) and two international news outlets (BBC and CNN). The findings show Indonesian news tends to make responsibility more visible by using material processes that clearly link actions to identifiable actors, which directly names Israeli military or state forces. In Indonesian local news more verbal processes are also used to give space to Palestinian voices rather than portraying them solely as voiceless victims. In contrast, international news tends to frame suffering through the dominant use of mental processes by focusing on emotions and internal states of the victims, making responsibility less visible. In semantic field distribution it is found that Indonesian local news uses more displacement-related processes compared to international news showing that western outlets limiting attention to the consequences of the conflict. Even so, both types of media tend to place Palestinian children in passive roles, with over 80% of material processes showing things being done to them rather than actions they take themselves. Overall, these findings reveal that linguistic choices in news reporting media are never neutral. They actively shape how responsibility, suffering, agency, and humanity are constructed in conflict coverage. This study contributes to SFL-based media discourse research and underlining the need for more accountable representation of vulnerable groups like children.